Simultaneous Determination of Polyamines and Steroids in Human Serum from Breast Cancer Patients Using Liquid Chromatography-Tandem Mass Spectrometry - Lee, Yu Ra; Lee, Ji Won; Hong, Jongki; Chung, Bong Chul (MDPI, 2021)
A simultaneous quantitative profiling method for polyamines and steroids using liquid chromatography-tandem mass spectrometry was developed and validated. We applied this method to human serum samples to simultaneously evaluate polyamine and steroid levels. Chemical derivatization was performed using isobutyl chloroformate to increase the sensitivity of polyamines. The method was validated, and the matrix effects were in the range of 78.7-126.3% and recoveries were in the range of 87.8-123.6%. Moreover, the intra-day accuracy and precision were in the ranges of 86.5-116.2% and 0.6-21.8%, respectively, whereas the inter-day accuracy and precision were in the ranges of 82.0-119.3% and 0.3-20.2%, respectively. The linearity was greater than 0.99. The validated method was used to investigate the differences in polyamine and steroid levels between treated breast cancer patients and normal controls. In our results, N-acetyl putrescine, N-acetyl spermidine, cadaverine, 1,3-diaminopropane, and epitestosterone were significantly higher in the breast cancer patient group. Through receiver operating characteristic curve analysis, all metabolites that were significantly increased in patient groups with areas under the curve >0.8 were shown. This mass spectrometry-based quantitative profiling method, used for the investigation of breast cancer, is also applicable to androgen-dependent diseases and polyamine-related diseases.